Jejak sejarah: a mobile application on Malaysian history for form four students with interactive notes and mind-map generator - Ismail, Muhammad Akram; Nasaruddin, Nor Intan Shafini (College of Computing, Informatics, and Mathematics, 2025)
The “Jejak Sejarah” mobile application was developed to enhance the learning experience of Malaysian history for Form Four students. The traditional methods of teaching history were often seen as monotonous, leading to reduced student engagement (Hassan & Mohamad, 2019). This study aimed to create an interactive learning tool incorporating gamification elements, quizzes, and a mind-map generator to improve learning outcomes. The development followed the ADDIE model, ensuring a systematic approach from analysis to evaluation (DeBell, 2020). The application provided chapter-based notes, interactive quizzes, and mind maps generated using Python and Graphviz (Xiao et al., 2023). The evaluation was conducted using the EGameFlow framework, measuring aspects such as concentration, goal clarity, feedback, and immersion (Fu, Su, & Yu, 2009). The results indicated that students found the application engaging and effective in enhancing their understanding of historical content. While some limitations were noted, such as incomplete syllabus coverage and lack of iOS support, future improvements could address these gaps. Overall, this project demonstrated the potential of mobile applications in making history learning more enjoyable and interactive for students.